ANALISIS PENGGUNAAN OBAT PADA PASIEN SIROSIS HATI BERDASARKAN VARIASI KOMPLIKASI DAN KONSEKUENSINYA TERHADAP BIAYA - , YENI FARIDA; , Dr. Tri Murti Andayani Sp.FRS., Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Liver cirrhosis enabling the occurrence of complications include portal hypertension, ascites, spontaneous bacterial peritonitis (SBP), esophageal varices, and hepatic encephalopathy. Therapy varies with increasing severity and complications that have an effect on the increase in costs. This study aims to determine the use of the drug in patients with liver cirrhosis according to the complications and consequences of the cost. The study design was observational analytic perspective of the hospital. Data were obtained by retrospective approach. Subjects were hospitalized cirrhosis patients in Dr. Sardjito in 2013 were determined by purposive sampling with the inclusion criteria of age â¥ 26 years, hospitalizations per 1 January to 31 December 2013 and the exclusion criteria were liver cirrhosis to liver cancer and incomplete data. The study subjects were 70 patients. Patient and drug data obtained from medical records while the cost data obtained from the information technology unit. The use of drugs was analyzed for compliance with the hospital standard and APASL guidelines, while the cost analysis done by analyzing the effect of complications and the severity of the increase in the cost using pearson correlation and linear regression. The results of this study show that most of the drug use are appropriate with hospital standard and APASL guideline. Inappropriate drug use are PPI and tranexamic acid for variceal esophagus hemorrage. Complications significant effect on the increase in drug costs. Severity and complications simultaneously significant effect on the increase in drug costs. Keywords: analysis of treatment, complications of liver cirrhosis, cost analysis